2022
DOI: 10.1155/2022/6969241
|View full text |Cite
|
Sign up to set email alerts
|

Scutellariae Radix and Citri Reticulatae Pericarpium Mixture Regulate PPARγ/RXR Signaling in Reflux Esophagitis

Abstract: Objective. Gastroesophageal reflux disease (GERD) is a gastrointestinal disorder in which stomach contents reflux into the esophagus, causing complications such as mucosal damage. GERD is a very common disease and is on the rise worldwide. The aim of this study was to assess the impact of a Scutellariae Radix and Citri Reticulatae Pericarpium mixture (SC) on esophageal mucosal injury in rats with chronic acid reflux esophagitis (CARE). Methods. After inducing reflux esophagitis through surgery, the group was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Pharmacological studies have found that when applied to the digestive system, the efficacy of CRP is to ameliorate gastrointestinal smooth muscle activity, accelerate gastric emptying and intestinal push, alter gut microbiota, protect the esophagus and gastrointestinal mucosa and resist peptic ulcer [ 2 , 3 , 4 , 5 , 6 , 7 ]. To date, CRP has proven effects in the respiratory system, including but not limited to inhibiting airway inflammation, fighting acute lung injury and pulmonary fibrosis [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Pharmacological Effects and Chemical Composition Of Crpmentioning
confidence: 99%
“…Pharmacological studies have found that when applied to the digestive system, the efficacy of CRP is to ameliorate gastrointestinal smooth muscle activity, accelerate gastric emptying and intestinal push, alter gut microbiota, protect the esophagus and gastrointestinal mucosa and resist peptic ulcer [ 2 , 3 , 4 , 5 , 6 , 7 ]. To date, CRP has proven effects in the respiratory system, including but not limited to inhibiting airway inflammation, fighting acute lung injury and pulmonary fibrosis [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Pharmacological Effects and Chemical Composition Of Crpmentioning
confidence: 99%